Moderating Effect of Customers’ Perceived Value of Retail Store on Relationship between Store Attribute and Customer Brand Loyalty - Siraphatthada, Yananda; Jankaweekool, Premkamon; Kilaso, Sathapath (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The aim of this study was to determine the moderating effect of customer perceived value to determine the relationship between stores attribute and customer brand loyalty in the case of the retail sector of Malaysia.Design/Method/Approach: This research has adopted a primary quantitative method where the instrument for data collection was a close-ended survey questionnaire. The survey was filled by 386 customers in Giant and Tesco retail store. SEM model was used to test the moderation of SmartPLS. The independent variable was store attribute and the dependent variable was customer brand loyalty. The moderating variables were hedonic value and utilitarian value. Findings: Findings has revealed that significant and positive relationship exists between store attributes and customer brand loyalty whereas, hedonic value moderates their relationship positively.Limitation: The major limitation of this research was the limited data, time and the number of stores selected for the collection of data.